(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article explores the integration of traditional and innovative methods within the educational process, with a particular focus on the pedagogy of Uzbekistan. It emphasizes analyzing key factors affecting teaching effectiveness, such as the relevance and value of educational content, students’ preparedness levels, and the use of a differentiated approach to instruction.